Suicídio e a rede de atenção psicossocial: um raio-x dos dispositivos de atendimento e prevenção em Manaus - Castro, Flávia Carolina Silva Santos de (Brasil, 2023)
Suicide is a public health problem that demands adequate attention from health systems. Based on this premise, the present study has the general objective of raising the challenges present in the health care network related to the care of suicide cases in the city of Manaus. As specific objectives, we seek to carry out a selection of historical-cultural conceptions about suicide and its psychosocial repercussions through a literature review on the subject; Map devices present on the network to assist suicide cases; Identify the challenges present in mental health services regarding suicide care and prevention. This article presents a qualitative field study whose methodology consisted of conducting semi-structured interviews with professionals in the field of mental health, in which the analysis was based on the epistemological perspectives of classical authors and on Bakhtin's discourse analysis. The results revealed categories such as the lack of understanding and invisibility of suicide, the network's prescribed performance and the actual performance, the challenges of care, including the lack of structure and the so-called "revolving door", in addition to the identification of the Amazonian logic as a potential for rethink mental health in the region. As a result, this study brings the challenges and perspectives related to the care of suicide cases in Manaus, exploring the local logic as a valuable approach to mental health in the region.